The Reconstruction of Logic of Language in the ‘Tractatus’ of L. Wittgenstein - Aukštuolytė, Nijolė (Problemos, 1985)
The problem of cognitive possibilities of the logic of language in science is analysed. Taking as an example the early works of L. Wittgenstein, the author tries to reveal the essence of logicism as an expression of formalism in gnoseological investigations. The inference is made that L. Wittgenstein seeking for the strict logico-linguistical determination has confined the problem of language in science within the logical conditions of linguistic behaviour.